Stable and reproducible MIP-ECL sensors for ultra-sensitive and accurate quantitative detection of Estrone - Cao, Jie; Chen, Xiao-Ying (Frontiers in Bioengineering and Biotechnology, 2024)
Estrone (E1), as an endogenous estrogen, has a variety of physiological functions in human body and is of great significance to human health. On the other hand, it is a widely distributed and highly disturbing environmental endocrine disruptor in water. Therefore, there is an urgent need to develop a sensitive, rapid, and inexpensive method for the on-site determination of E1, which is not only for clinical diagnosis and treatment, but also for the investigation and monitoring of endogenous estrogen pollution in environmental water. In this study, Ru(bpy)32+/MWCNTs/Nafion/gold electrodes were prepared by surface electrostatic adsorption and ion exchange. A molecularly imprinted membrane (MIP) with the capability to recognize E1 molecules was prepared by sol-gel method, and the electrodes were modified with MIP to form an electrochemical luminescence sensor (MIP-ECL). This method simultaneously possesses ECL’s advantage of high sensitivity and MIP’s advantage of high selectivity Moreover, the addition of carboxylated multi-walled carbon nanotubes (MWCNT-COOH) improved the functionalization of the gold electrode surface and increased the binding sites of MIP. Meanwhile, the good conductivity of MWCNTs promoted electron transfer and further improved the sensitivity of the sensor. The sensor showed a wide linear interval in which the E1 concentrations can range from 0.1 µg/L to 200 µg/L, along with a high linear correlation coefficient (R2 = 0.999). The linear regression equation of the sensor was Y=243.64x-79.989, and the detection limit (LOD) was 0.0047 µg/L. To validate our sensor, actual samples were also measured by the reference method (LC-MS/MS), and it was found that the relative deviation of quantitative results of the two different methods was less than 4.1%. This indicates that the quantitative results obtained by this sensor are accurate and can be used for rapid in situ determination of E1 in clinical samples and environmental water.